Caracterização microbiológica e fisico-química durante a maturação em diferentes épocas do ano de queijo Minas artesanal de produtores cadastrados da mesorregião de Campo das Vertentes - MG - Leticia Goulart de Oliveira (2014)
Artisanal Minas cheese is made under small scale production, using traditional methods and raw cows' milk. Environmental, socio-economical, and livestock factors, allied with an indigenous microbiota, allow unique cheese characteristics, such as flavor and appearance. There have been few researches focusing on this specific cheese from Campo das Vertentes. Hence, the aim of this study was to specify the microbiological and physical-chemical characteristics of artisanal Minas cheese from registered cheese producers from Campo das Vertentes, during a sixty-day ripening and in two different seasons, summer and winter (rainy and dry seasons). There were not any differences on the counts of moulds and yeasts and on the percentage of total solids, water content, fat and total nitrogen when seasons were compared. However, the counts of total and thermotolerant coliforms, and Staphylococcus coagulase positive were higher during the summer, whilst the counts of acid lactic bacteria on MRS agar and M17 agar were higher in the dry season. Salmonella spp. were not detected in any sample inspected. During the sixty-day ripening, the counts of lactic acid bacteria, on both agars, became inferior only during winter. The counts of the other microorganisms were the same throughout the ripening, specially because of post-contamination as aging. The same happened with pH and with the percentage of titratable acidity. Nonetheless, the percentage of total solids, water content, fat, and total nitrogen diverged mainly because of concentration by evaporation of water. Therefore, the ripening process is one single step in the achievement of an innocuous artisanal Minas cheese. Conclusively, this study has allowed a broader knowledge of the artisanal Minas cheese from registered producers from Campo das Vertentes and can be seen as a preliminary investigation on the matter.